Use of steel fiber reinforced concrete for blast resistant design - Kalman, Deidra (Kansas State University, 2010)
Reinforced concrete is a common building material used for blast resistant design. Adding fibers to reinforced concrete enhances the durability and ductility of concrete. This report examines how adding steel fibers to reinforced concrete for blast resistant design is advantageous. An overview of the behavior of blasts and goals of blast resistant design, and advantages of reinforced concrete in blast-resistant design, which include mass and the flexibility in detailing, are included in the blast resistant design section. The common uses for fiber-reinforced concrete, fiber types, and properties of fiber reinforced concrete varying with fiber type and length, and concrete strength are discussed in the fiber-reinforced concrete section. Two studies, Very High-Strength Concrete for Use in Blast-and-Penetration Resistant Structures and Blast Testing of Ultra-High Performance Fiber and FRP-Retrofitted Concrete Slabs, are reviewed. Lastly, the cost, mixing and corrosion limitations of using steel fiber-reinforced concrete are discussed. Reinforced concrete has been shown to be a desirable material choice for blast resistant design. The first step to designing a blast resistant reinforced concrete structure is to implement proper detailing to ensure that structural failures will be contained in a way that preserves as many lives as possible. To design for the preservation of lives, a list of priorities must be met. Preventing the building from collapse is the first of these priorities. Adding steel fibers to concrete has been shown to enhance the concrete’s post-crack behavior, which correlates to this priority. The second priority is reducing flying debris from a blast. Studies have shown that the failure mechanisms of steel fiber reinforced concrete aid in reducing flying debris when compared to conventional reinforced concrete exposed to blast loading. The major design considerations in designing steel fiber reinforced concrete for blast resistant design include: the strength level of the concrete with fiber addition, fiber volume, and fiber shape. As research on this topic progresses, the understanding of these factors and how they affect the strength characteristics of the concrete will increase, and acceptance into the structural design industry through model building codes may be possible.
Keywords: Blast resistant design; Fiber reinforced concrete; Engineering, Civil (0543)